2004
DOI: 10.1038/sj.tpj.6500282
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to Tardive Dyskinesia in chronic schizophrenia subjects: I. Association of CYP1A2 gene polymorphism

Abstract: Understanding the pharmacogenetic basis of developing iatrogenic disorders such as Tardive Dyskinesia (TD) has significant clinical implications. CYP1A2, an inducible gene of the cytochrome P450 family of genes, has been suggested to contribute to the metabolism of typical antipsychotics in subjects with schizophrenia on long-term treatment, and has been considered as a potential candidate gene for development of TD. In this study, we have investigated the significance of CYP1A2 gene polymorphisms in TD suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 41 publications
(51 reference statements)
1
57
1
2
Order By: Relevance
“…As a wide range of CYP450 genes and outcome measures were included in these studies, it is difficult to generalize the findings although no evidence for an association between outcome and genotype was apparent in any individual study with two exceptions in small studies of CYP2D6 that must be treated with extreme caution: a greater proportion of patients with the mut/mut genotype (4/5) experienced general chronic movement disorders than either the wt/wt CYP450 testing for prescribing antipsychotics in adults with schizophrenia N Fleeman et al (18/43) or wt/mut (13/23) genotypes 57 and patients with a wt/mut (5/11) genotype taking olanzapine experienced a statistically significantly larger percentage change in body mass index than patients in the wt/wt group (6/11). 63 CYP1A2 enzyme activity is commonly considered to be affected by smoking; 105 in the current review, only one CYP1A2 study reported pronounced increased effects in terms of Abnormal Involuntary Movement Scale scores in patients who were documented smokers, 60 whereas another four studies 61,74,79,87 failed to report such an association. In addition, a small study 65 of CYP2D6 also reported that differences in Abnormal Involuntary Movement Scale scores between genotype groups were only significant in smokers.…”
Section: Clinical Validitymentioning
confidence: 61%
See 1 more Smart Citation
“…As a wide range of CYP450 genes and outcome measures were included in these studies, it is difficult to generalize the findings although no evidence for an association between outcome and genotype was apparent in any individual study with two exceptions in small studies of CYP2D6 that must be treated with extreme caution: a greater proportion of patients with the mut/mut genotype (4/5) experienced general chronic movement disorders than either the wt/wt CYP450 testing for prescribing antipsychotics in adults with schizophrenia N Fleeman et al (18/43) or wt/mut (13/23) genotypes 57 and patients with a wt/mut (5/11) genotype taking olanzapine experienced a statistically significantly larger percentage change in body mass index than patients in the wt/wt group (6/11). 63 CYP1A2 enzyme activity is commonly considered to be affected by smoking; 105 in the current review, only one CYP1A2 study reported pronounced increased effects in terms of Abnormal Involuntary Movement Scale scores in patients who were documented smokers, 60 whereas another four studies 61,74,79,87 failed to report such an association. In addition, a small study 65 of CYP2D6 also reported that differences in Abnormal Involuntary Movement Scale scores between genotype groups were only significant in smokers.…”
Section: Clinical Validitymentioning
confidence: 61%
“…58,60,70,76,78,96 In the remaining 42/51 studies, it was unclear whether the number contributing to each analysis was equal to the sample size. No study mentioned conducting specific tests for population stratification even though six 57,60,87,96,102,103 were known to include patients with different ethnic backgrounds. A minority (21/51) of studies [59][60][61][62]66,67,70,72,74,[76][77][78][79]81,82,[85][86][87][88]96,100 reported testing for Hardy-Weinberg equilibrium.…”
Section: Clinical Validitymentioning
confidence: 99%
“…CYP1A2 has not been reported to metabolize risperidone; however, a minor role of this gene has been ascribed in case of olanzapine metabolism. 19 Thus, our observation of lack of significant association of CYP1A2 1545C4T (this study), CYP1A2*1C or CYP1A2*1F 14 with the development of TD seems appropriate. Further, the only variability in the metabolism by CYP1A2 has been associated with the induction by smoking.…”
Section: Discussionmentioning
confidence: 72%
“…14 To rule out the contribution of other reported polymorphisms from the coding region of this gene to the differential activity and thus to the development of TD, we genotyped four reported nonsynonymous amino-acid substitutions 16 but these were found to be monomorphic in our population. 14 In order to screen the coding region for any novel polymorphism, we sequenced the seven exons of CYP1A2 gene. Nonsynonymous polymorphisms were not observed in the exons; however, a previously reported synonymous polymorphism in exon 7 CYP1A2 1545 C4T (N515 rs2470890) along with three other intronic polymorphisms were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation